A novel model predictive control with an integrated SOC and floating DC-link voltage balancing for 3-phase 7-level PUC converter-based MV BESS. (September 2021) - Khalid, Hassan Abdullah; Al-Emadi, Nasser Ahmed; Ben-Brahim, Lazhar; Gastli, Adel; Cecati, Carlo
Highlights: A novel control scheme for a PUC inverter has been proposed for the BESS application. The proposed scheme uses a finite-set MPC with an inner and outer loop. Good dynamic performance and fault-ride-through capability have been achieved. Grid code compliance at low switching frequency has been demonstrated. Abstract: Compared to conventional multilevel topologies, the Packed U-Cell multilevel topology utilizes the minimum number of components and provides both maximum voltage levels and high reliability. When used in a battery energy storage system, its dc-link consists of a top branch battery storage and bottom branch flying capacitors, whose state of charge and voltages must be balanced.This paper proposes a novel control scheme with two cascaded controllers: the inner loop regulates the output filter current and dc-link voltages using a novel finite-set model predictive control, the outer one is fully integrated with the model predictive controller and regulates the battery state of charge by injecting a zero-sequence voltage. The proposed control scheme was successfully implemented and tested through simulation and real-time testing. The obtained results highlight good dynamic performance and robustness of the proposed scheme during active power injection/absorption and low voltage ride-through capability.